Homogenisasi Sekunder terhadap Kadar Hemoglobin - Rosnita Sebayang; Hotman Sinaga; Mustika Sari Hutabarat (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the results of hemoglobin examination with secondary homogenization techniques 3, 5, 7, and 8 times, after being left for 60 minutes after primary homogenization. The research method used is pre-experimental research. The results showed that the average hemoglobin measured by an automatic hematology analyzer in the secondary homogenized blood group was 3 times 13.3 g/dl, homogenized 5 times 13.1 g/dl, homogenized 7 times 13.2 g/dl, and homogenization 8 times 13.1g/dl. In conclusion, there is no difference in hemoglobin levels in the secondary homogenization process 3, 5, 7, and 8 times. Keywords: EDTA Blood, Hemoglobin, Homogenization